Thermoregulation by an Australian murine rodent, the ash-grey mouse (Pseudomys albocinereus) - Barker, Justine M.; Cooper, Christine E.; Withers, Philip C.; Cruz-Neto, Ariovaldo P. [UNESP] (Elsevier B.V., 2012)
We examine here the thermal physiology of the ash-grey mouse, as there is a paucity of data to explain how Australian rodents meet thermoregulatory demands. Most ash-grey mice remained normothermic over a range of ambient temperatures (10 degrees C to 30 degrees C), although they became hyperthermic at high ambient temperatures. One individual entered torpor at ambient temperatures of 20 degrees C and 25 degrees C, with minimal body temperatures of 24.5 degrees C and 28.4 degrees C respectively, before spontaneously arousing. This is the first evidence of torpor use by an Australian murine rodent. Our data suggest that although ash-grey mice have the physiological ability to use torpor, it is used rarely, presumably due to other behavioural and physiological adaptations. Their higher-than-expected basal metabolic rate (1.56 +/- 0.25 mL O-2 g(-1) h(-1)) indicates that ash-grey mice do not have a frugal approach to energy expenditure. Other standard physiological variables were typical of a generalised rodent. A readily-available omnivorous diet, nocturnal activity, semi-fossorial habit and social behaviour presumably allow a high energy lifestyle. A reluctance to use torpor, despite an apparent physiological ability to do so, supports the idea that the use of torpor reflects a net balance between the costs and benefits of a heterothermic thermoregulatory strategy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Body temperature; Evaporative water loss; Heterothermy; Rodent; Metabolic rate; Torpor; Water economy